Total Knee Arthroplasty in a Patient with Bilateral Congenital Dislocation of the Patella Treated with a Different Method in Each Knee - Hajime Yamanaka; Taisei Kawamoto; Hiroshi Tamai; Munetaka Suzuki; Tatsuya Kobayashi; Yawara Eguchi; Hideyuki Nakajima (Case Reports in Orthopedics)
We have operated total knee arthroplasty in a patient with bilateral congenital dislocation of the patella treated with a different method in each knee.